الأطر التشريعية والتنظيمية للاقتصاد الرقمي بين طموح الأهداف التنظيمية وتحديات الواقع الاجتماعي - بن علي, امحمد; رزقي, نوال (University of Eloued جامعة الوادي, 2022)
تعالج المداخلة إشكالية مهمة جدا، تشكّل تحديا كبيرا للدول النامية، وهي الهوة القائمة بين متطلبات اعتماد الاقتصاد الرقمي كمنظومة قانونية متكامل ة، تستهدف خلق ديناميكية اقتصادية قوية بعد الركود الحاصل جراء أزمة جائحة كورونا و التداعيات الاقتصادية المتزايدة للحرب في أوكرانيا من جهة، والواقع الاجتماعي المعقّد الذي تتخبطّ فيه جل تلك الدول وتجد صعوبة كبيرة في تجاوزه من جهة ثانية، لأنه ببساطة أصبح بمثابة الوضع الطبيعي بالنسبة لفئات واسعة من المجتمع، التي تعودّت عليه وباتت تجد معالِمها فيه، حتى و إن كان فوضوياّ وغير قابل للإصلاح و التطوير . Abstract: The current paper discusses a very important problematic, representing a big challenge to the Developing Countries. This problematic is the existing gap between the conditions of adapting the digital economy as an integral legal system. This last aims at creating a strong economy dynamic, particularly after the recession caused by Corona Pandemic and the economic consequences of the war in Ukraine on one hand, yet the social complex reality disturbing most of those countries already finding difficulties to overcome it on the other hand. This became simply a normal situation for large categories of the society, which got used to it and started to find its features in it, even though it is chaotic, beyond repair and development.
Legislative and regulatory frameworks for the digital economy between the ambition of organizational goals and the challenges of social reality
مداخلة. الملتقى الدولي الافتراضي حول: البيانات الضخمة والاقتصاد الرقمي كآلية لتحقيق الإقلاع الاقتصادي في الدول النامية "الفرص، التحديات والآفاق"
Keywords: الاقتصاد الرقمي، المورّد الالكتروني، المستهلك الالكتروني، المشرّع الجزائري، الواقع الاجتماعي .; Digital Economy; Electronic Supplier; Electronic Consumer; Algerian Legislature; Social Reality.